Gene cloning and difference analysis of vitellogenin in Neoseiulus barkeri (Hughes). Issue 2 (11th July 2017) - Ding, L.; Chen, F.; Luo, R.; Pan, Q.; Wang, C.; Yu, S.; Cong, L.; Liu, H.; Li, H.; Ran, C.
Abstract: Neoseiulus barkeri (HUGHES) is the natural enemy of spider mites, whiteflies and thrips. Screening for chemically-resistant predatory mites is a practical way to balance the contradiction between the pesticide using and biological control. In this study, the number of eggs laid by fenpropathrin-susceptible and resistant strains of N. barkeri was compared. Additionally, we cloned three N. barkeri vitellogenin (Vg) genes and used quantitative real-time polymerase chain reaction to quantify Vg expression in susceptible and resistant strains. The total number of eggs significantly increased in the fenpropathrin-resistant strain. The full-length cDNA cloning of three N. barkeri Vg genes ( NbVg1, NbVg2 and NbVg3 ) revealed that the open reading frames of NbVg1, NbVg2 and NbVg3 were 5571, 5532 and 4728 bp, encoding 1856, 1843 and 1575 amino acids, respectively. The three N. barkeri Vg possessed the Vitellogenin-N domain (or lipoprotein N-terminal domain (LPD_N)), von Willebrand factor type D domain (VWD) and the domain with unknown function 1943 (DUF1943). The NbVg1 and NbVg2 expression levels were significantly higher in the resistant strain than in the susceptible strain, while the NbVg3 expression level was lower in the resistant strain. Thus, we speculate that the increased number of eggs laid by the fenpropathrin-resistant strain of N. barkeri may be a consequence of changes in Vg gene expression.